A experimentação em sala de aula promovendo a associação entre teoria e prática - SOUSA, Félix Júnior Pantoja de (2021)
This study aimed to insert classroom experimentation to promote the association between theory and practice of hydrostatic concepts. To this end, a field research was conducted at Pedro Teixeira State School - Annex I / Abaetetuba - PA, with the students of the first year of high school and the class Physics teacher. Along with this sample group, the following methodological procedures were performed: interview with the educator, pre-test, two theoretical classes, workshop, post-test and investigative questionnaire. In the workshop, experiments were carried out with accessible and low cost materials with the students to help in understanding the concepts studied in the lectures. As the educational institution did not have a science laboratory, the demonstrations were made in the classroom itself and were attended by all students. In addition to the motivational aspect verified, it was noted that the use of experiences helped in the significant understanding of the concepts taught, since there was a better performance of students in the post-test and the students themselves reported in the investigative questionnaire that the workshop had an important role in understanding of the content worked. Moreover, this research showed that the structural and material conditions of the school affect the teaching work, especially regarding the performance of experimental activities.